In Vitro Micropropagation of Fritllaria imperialis and F. persica using Different Portions of Leaf as Explant - Kizil, Suleyman; Khavar, Khalid Mahmood; Sesiz, Ugur (Univ Agriculture, Fac Veterinary Science, 2024)
Fritillaria imperialis and F. persica are important ornamental and medicinal plant species that grow naturally in large areas of the Middle East, Central, and Western Asia. These are counted as neglected crops and face lack of appropriate agronomic and biotechnological attention in development of propagation technologies. Therefore, the study aimed to micro propagate these two species using new explants of apical, middle, and basal portions of leaf from newly germinated seedlings for direct bulblet regeneration. The results testified the regeneration competency of the three explants of each species on six sets of naphthalene acetic acid (NAA) - benzyl aminopurine (BAP) modified Murashige and Skoog (MS) medium. The maximum number of 2.48 and 2.04 bulblets per explant on F. imperialis and F. persica was induced on basal portions of leaf on MS medium modified with 0.15 mg L-1 NAA+2.0 mg L-1 BAP and 0.1 mg L-1 NAA+2.0 mg L-1 BAP respectively. The regenerated bulblets were rooted on MS medium modified with 0.5 mg L(-1 )NAA and acclimatized in pots containing peat moss. Regardless of the explant types obtained from each species, all explants had the competence to regenerate new bulblets. A comparative analysis of morphological features of in vitro-grown plants with field-grown plants showed similarities. It was concluded that these methodologies could be exploited further for commercial micropropagation of both species without compromising the quality of the mother species.
Keywords: Fritillaria species; plant growth regulators; leaf-based explants; regeneration; rooting